2001
DOI: 10.1002/1522-2683(200109)22:16<3573::aid-elps3573>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a functional group in penicillin derivatives on the interaction with bile salt micelles studied by micellar electrokinetic chromatography

Abstract: A capillary electrophoresis method is developed and validated for the characterization of the affinity and the interaction between aminopenicillanic acid (APS-H) and its derivatives with bile salt micelles. The micellar systems studied contained sodium taurocholate (NaTC) and sodium deoxycholate (NaDC). Using the retention factor k', functional group selectivity, gammaG, is defined as the ratio of the retention factor of a substituted aminopenicillanic acid (APS-R) over the capacity factor of APS-H and the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Highly hydrophilic neutral compounds such as acetone are used as EOF markers, whereas highly lipophilic compounds such as dodecaphenone are selected as micelle markers. Good linear correlations were found between log k (measured by MEKC) and log P oct for a wide variety of compounds and conditions [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. However, congeneric behavior was observed [108,116] and confirmed by LSER analyses, which demonstrated differences in H-bond basicity and dipolarity/polarizability for partitioning into SDS micelles or the 1-octanol/ water system [98].…”
Section: Theory and Principlesmentioning
confidence: 68%
“…Highly hydrophilic neutral compounds such as acetone are used as EOF markers, whereas highly lipophilic compounds such as dodecaphenone are selected as micelle markers. Good linear correlations were found between log k (measured by MEKC) and log P oct for a wide variety of compounds and conditions [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. However, congeneric behavior was observed [108,116] and confirmed by LSER analyses, which demonstrated differences in H-bond basicity and dipolarity/polarizability for partitioning into SDS micelles or the 1-octanol/ water system [98].…”
Section: Theory and Principlesmentioning
confidence: 68%
“…Bile salts have been shown to increase intestinal absorption of insulin (14), cefpirom (15) and many other drugs. It has been shown that MKC improved the absorption and blood-brain barrier penetration of morphine and quinidine (16) as well as the hypoglycemic effect of insulin (17).…”
Section: 'Introductionmentioning
confidence: 99%
“…Good correlation between MEKC log k 0 for six -blockers to Caco-2 cell permeability was also shown, as was permeation through the intestinal segment of rat ileum and rat colon data (Ö rnskov et al 2000). Good correlation with permeation across a dodecanol collodium cell membrane system has also been reported (Mrestani et al 2001). MEKC migration data were correlated to Caco-2 cell permeability data for -blocker model compounds (Detroyer et al 2003).…”
Section: Introductionmentioning
confidence: 67%